New factors contributing to dynamic calcium regulation in the skeletal muscle triad-a crowded place - Friedrich, Oliver; Fink, Rainer; von Wegner, Frederic (Biophysical Reviews, 2010)
Skeletal muscle is a highly organized tissue that has to be optimized for fast signalling events conveying electrical excitation to contractile response. The site of electro-chemico-mechanical coupling is the skeletal muscle triad where two membrane systems, the extracellular t-tubules and the intracellular sarcoplasmic reticulum, come into very close contact. Structure fits function here and the signalling proteins DHPR and RyR1 were the first to be discovered to bridge this gap in a conformational coupling arrangement. Since then, however, new proteins and more signalling cascades have been identified just in the last decade, adding more diversity and fine tuning to the regulation of excitation-contraction coupling (ECC) and control over Ca store content. The concept of Ca entry into working skeletal muscle has become attractive again with the experimental evidence summarized in this review. Store-operated Ca entry (SOCE), excitation-coupled Ca entry (ECCE), action-potential-activated Ca current (APACC), and retrograde EC-coupling (ECC) are new concepts additional to the conventional orthograde ECC; they have provided fascinating new insights into muscle physiology. In this review, we discuss the discovery of these pathways, their potential roles, and the signalling proteins involved that show that the triad may become a crowded place in time. © 2009 International Union for Pure and Applied Biophysics (IUPAB) and Springer.
Keywords: Action-potential-activated Ca2+ entry; Ca2+ sparks; DHPR; Excitation-coupled Ca2+ entry; Retrograde coupling; RyR; Skeletal muscle; Store-operated Ca2+ entry; T-system; Triad